The Power of Primary Schools to Change and Sustain Handwashing with Soap among Children : The Cases of Vietnam and Peru - Dutton, Pennelope; Peschiera, Rocio Florez; Nguyen, Nga Kim (World Bank, Washington, DC, 2014)
Vietnam and Peru are two of four countries taking part in the Water and Sanitation Program (WSP) Global Scaling up Handwashing Project. Funded by the Bill and Melinda Gates Foundation, the Global Scaling Up Handwashing Project aims to expand handwashing practices among women of reproductive age (15-49 years) and primary school-aged children (5 to 12 in Peru; 6 to 10 in Vietnam) The project focuses on applying innovative promotional approaches to generate widespread and sustained improvement in handwashing with soap practice. Started in December 2006, the project is implemented by local and national governments with technical support from WSP, and participation from the private sector and nongovernmental organizations. The present document describes the approaches to changing children's handwashing with soap behavior, first in Vietnam, then Peru, followed by some lessons learned and conclusions.